1992
DOI: 10.1126/science.1589767
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of phonetic and pitch discrimination in speech processing

Abstract: Cerebral activation was measured with positron emission tomography in ten human volunteers. The primary auditory cortex showed increased activity in response to noise bursts, whereas acoustically matched speech syllables activated secondary auditory cortices bilaterally. Instructions to make judgments about different attributes of the same speech signal resulted in activation of specific lateralized neural systems. Discrimination of phonetic structure led to increased activity in part of Broca's area of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

108
640
11
13

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,365 publications
(772 citation statements)
references
References 32 publications
108
640
11
13
Order By: Relevance
“…The temporal activation (superior temporal region; STR) is in line with previous fMRI results on spoken words (e.g., Binder et al, 2000) and sentence comprehension (e.g., Dehaene et al, 1997;Friederici, Meyer, & von Cramon, 2000;Meyer et al, 2002;Meyer, Friederici, & von Cramon, 2000) as well as studies on the perceptual analysis of speech signals (Hickok & Poeppel, 2000;Zatorre, Evans, Meyer, & Gjedde, 1992). Activation of the STR was extremely reduced for prosodic speech.…”
Section: Temporal Activationsupporting
confidence: 88%
“…The temporal activation (superior temporal region; STR) is in line with previous fMRI results on spoken words (e.g., Binder et al, 2000) and sentence comprehension (e.g., Dehaene et al, 1997;Friederici, Meyer, & von Cramon, 2000;Meyer et al, 2002;Meyer, Friederici, & von Cramon, 2000) as well as studies on the perceptual analysis of speech signals (Hickok & Poeppel, 2000;Zatorre, Evans, Meyer, & Gjedde, 1992). Activation of the STR was extremely reduced for prosodic speech.…”
Section: Temporal Activationsupporting
confidence: 88%
“…showed that the perceptual analysis of normal speech signals is subserved by the temporal lobes [Zatorre et al, 1992]. A similar explanation is given by Hickok and Poeppel [2000], who also argue that the soundbased representation of speech is located in the posterior-superior temporal region bilaterally.…”
Section: Figuresupporting
confidence: 57%
“…Furthermore we predict to find decreased responses to prosodic speech in the auditory cortex bilaterally because the total amount of auditory information contained in prosodic speech is clearly reduced relative to normal and syntactic speech. According to recent PET-studies on pitch perception [Gandour et al, 2000;Zatorre et al, 1992Zatorre et al, , 1994] a bilateral engagement of the inferior frontal cortex is also likely. The data at hand, however, allow no clear prediction with respect to the lateralization of the frontal activation: although processing pitch variations in a grammatically relevant context was shown to occur in the left fronto-opercular cortex [Gandour et al, 2000], pitch processing of complex auditory stimuli in a nonlinguistic context rather revealed either right dorsolateral activation [Zatorre et al, 1992] or bilateral contributions of the frontal operculum [Zatorre et al, 1994].…”
Section: Present Studymentioning
confidence: 99%
“…Stimuli based on fundamental frequency (F0) have generally been found to show right-hemisphere lateralization (e.g., Blumstein and Cooper, 1974, for intonation contours; Goodglass and Calderon, 1977, for musical notes; Mazzucchi et al, 1981, for synthesized tones). For example, prefrontal cortex in the right hemisphere has been linked to pitch judgment tasks (Zatorre et al, 1992) and music processing (Pugh et al, 1996a,b). Consequently, the right hemisphere, especially the right inferior frontal gyrus, can play a significant role in tone production.…”
Section: Discussionmentioning
confidence: 99%